Effect of Human Urine on Cell Cycle and Infectivity of Leismania Species Promastigotes In Vitro - Allahverdiyev, Adil M.; Bagirova, Melahat; Elcicek, Serhat; Koc, Rabia Cakir; Oztel, Olga N. (Amer Soc Trop Med & Hygiene, 2011)
In vitro cultivation of Leishmania parasites plays an important role in diagnosis and treatment of leishmaniasis and in vaccine and drug development studies. Conversely, long-term cultivation of Leishmania parasites usually results in decreased infectivity potential. Some studies reported a stimulatory effect of human urine in Leishmania promastigotes. However, there is no information about the effects of urine within culture on the infectivity of Leishmania parasites. Analysis of the effect of urine have showed that proliferation indexes were significantly increased in culture medium supplemented with human urine (L. tropica = 38.17 +/- 5.12, L. donovani = 34.74 +/- 5.6, L. major = 34.22 +/- 4.66, and L. infantum 35.88 +/- 6.40) than in controls. Infection indexes were 13 +/- 1.7 for L. tropica, 55 +/- 2.2 for L. infantum, 41 +/- 3.14 for L. donovani, and 49 +/- 3.26 for L. major. Our results showed that human urine increased the infectivity and proliferation of Leishmania parasites.
Keywords: Leishmania-Donovani Promastigotes; Stimulates Growth; Cultivation; Culture; Parasite; Macrophages; Virulence; Media; Differentiation; Amazonensis